Merkel cell polyomavirus small T antigen is oncogenic in transgenic mice - Verhaegen, Monique E. (J Invest Dermatol, 2014)
Merkel cell carcinoma (MCC) is a rare and deadly neuroendocrine skin tumor frequently associated with clonal integration of a polyomavirus, MCPyV, and MCC tumor cells express putative polyomavirus oncoproteins small T antigen (sTAg) and truncated large T antigen (tLTAg). Here, we show robust transforming activity of sTAg in vivo in a panel of transgenic mouse models. Epithelia of pre-term sTAg-expressing embryos exhibited hyperplasia, impaired differentiation, increased proliferation and apoptosis, and activation of a DNA damage response. Epithelial transformation did not require sTAg interaction with the PP2A protein complex, a tumor suppressor in some other polyomavirus transformation models, but was strictly dependent on a recently-described sTAg domain that binds Fbxw7, the substrate-binding component of the SCF ubiquitin ligase complex. Postnatal induction of sTAg using a Cre-inducible transgene also led to epithelial transformation with development of lesions resembling squamous cell carcinoma in situ and elevated expression of Fbxw7 target proteins. Our data establish that expression of MCPyV sTAg alone is sufficient for rapid neoplastic transformation in vivo, implicating sTAg as an oncogenic driver in MCC and perhaps other human malignancies. Moreover, the loss of transforming activity following mutation of the sTAg Fbxw7 binding domain identifies this domain as crucial for in vivo transformation.